2016
DOI: 10.1158/0008-5472.can-14-0673
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase PTP4A3 Promotes Triple-Negative Breast Cancer Growth and Predicts Poor Patient Survival

Abstract: Triple-negative breast cancer (TNBC) has the worst prognosis of all breast cancers, and women diagnosed with TNBC currently lack targeted treatment options. To identify novel targets for TNBC, we evaluated phosphatase expression in breast tumors and characterized their contributions to in vitro and in vivo growth of TNBC. Using Affymetrix microarray analysis of 102 breast cancers, we identified 146 phosphatases that were significantly differentially expressed in TNBC compared to estrogen receptor (ER)-positive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 33 publications
1
70
0
Order By: Relevance
“…While another group has preliminarily reported the in vivo effects of knocking down PRL-3 on primary TNBC tumor growth [41], studies examining the effects of PRL-3 knock down or AMPI-109 treatment on invasive and metastatic endpoints in TNBC animal models are urgently needed. Our laboratory is currently pursuing these studies.…”
Section: Discussionmentioning
confidence: 99%
“…While another group has preliminarily reported the in vivo effects of knocking down PRL-3 on primary TNBC tumor growth [41], studies examining the effects of PRL-3 knock down or AMPI-109 treatment on invasive and metastatic endpoints in TNBC animal models are urgently needed. Our laboratory is currently pursuing these studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, analysis of publicly available breast cancer datasets revealed that PTP4A3 expression is significantly elevated in TNBC samples, and in silico analysis revealed that increased PTP4A3 expression is due to gene amplification in 29% of basal like breast cancers. Depletion of PTP4A3 reduced TNBC tumor growth in vivo by reducing proliferation marker (Ki67), phospho-ERK1/2 and p38 levels, while increasing apoptotic markers (1). Highly elevated PTP4A3 expression is also associated with enhanced tumor formation and metastasis by reducing tumor initiating cells in colon cancer mouse models (46).…”
Section: Phosphatases As Oncogenesmentioning
confidence: 99%
“…den Hollander et al (2016), explored the expression levels of PTPs in 102 human breast cancer samples to identify PTPs that are differentially overexpressed in triple-negative breast cancer (TNBC). In this study, 146 PTPs were differentially expressed in TNBC as compared to estrogen receptor-positive (ER-positive) breast cancer samples.…”
Section: Phosphatases As Oncogenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Elegant studies described the amplification of the PRL-3 gene ( PTP4A3 ) in the chromosomal region 8q24.3 in colon cancer metastases [4], breast [21], and gastric carcinomas [22]. Gene amplification is a mechanism to enhance gene expression of oncogenes and could explain PRL-3 overexpression in some human cancer types [4].…”
Section: Introductionmentioning
confidence: 99%